Биотехнические системы управления двигательными функциями человека - Вовк, М.И. (Кибернетика и вычислительная техника, 2017)
Рассмотрена эволюция синтеза биотехнических систем управления двигательными функциями как внешних контуров управления — «Миотон», «Миокор», адаптивных «Миостимул», используемые для восстановления двигательных функций. Представлен новый класс электронных аппаратов цифровой медицины, персональных, биологически адекватных «Тренар». Теоретической основой синтеза таких систем является обработка электромиографических (ЭМГ) сигналов. Адекватность воздействий состоянию двигательных функций, этапу их восстановления обеспечивается различными программами и методами управления. Рассмотрена оригинальная технология управления тонкой моторикой кисти для восстановления речи на базе аппаратов «Тренар». Розглянуто еволюцію синтезу біотехнічних систем керування руховими функціями, як зовнішніх контурів керування — «Міотон», «Міокор», адаптивних «Міостимул», які використовуються для відновлення рухових функцій. Представлено новий клас електронних апаратів цифрової медицини, персональних, біологічно адекватних «Тренар». Теоретичною основою синтезу таких систем є обробка електроміографічних (ЕМГ) сигналів. Адекватність керування стану рухових функцій і етапу їх відновлення забезпечується різними програмами і методами. Розглянуто оригінальну технологію керування тонкою моторикою кисті для відновлення мовлення на базі апаратів «Тренар». The purpose of the article is to present the results of theoretical and applied researches focused on synthesis of information technologies for human motion control based on bioengineering systems as external control circuits. Results. The evolution of bioengineering systems for motor control — multichannel electronic devices "Mioton-2", "Mioton-3M", "Mioton-604", "Miokor", adaptive device "Miostimul" and a new class of portable electronic devices of digital medicine for personal, biologically adequate, motor control "TRENAR®" are considered. Special EMG — signals processing and its transformation into informative visual and sound signals, that describe muscle contractions are used to develop different programms for muscle control. These programs based on different methods of muscle electrical stimulation and biofeedback are aimed on activaton of additional brain reserves to restore motor functions. New method and technology to restore motor speech, based on original technique of fine motor hand training by the technology “Trenar” is described. The results of clinical testing confirmed its effectiveness in motor speech restoration after the stroke.